False Positive Ventilation/Perfusion SPECT/CT Mismatch Mimicking Pulmonary Embolism in a Patient With Bilateral Lung Transplant. (18th November 2022) - Sandach, Patrick; Kleibrink, Björn; Maier, Sandra; Herrmann, Ken; Hautzel, Hubertus
Abstract: Ventilation/perfusion SPECT/CT has very high sensitivity with little false-positive findings for diagnosing pulmonary embolism (PE). However, bronchopulmonary tumors or structural changes of the lungs' vasculature infrequently mimic PE. Here, a 59-year-old man presented with acute dyspnea and acute renal failure 5 years after bilateral lung transplant. Pulmonary ventilation/perfusion SPECT/CT was performed demonstrating a lobar mismatch of the left upper lung lobe indicative for PE. Bronchoscopy revealed local hyperemia of this lobe, indicating prolonged venous blood return. Subsequent CT angiography confirmed postsurgical upper pulmonary vein obliteration as final diagnosis. In conclusion, pulmonary vein obliteration might cause false-positive ventilation/perfusion SPECT/CT.